Cycloartanes from Krameria pauciflora and Their In Vitro PLA2, COX-1, and COX-2 Enzyme Inhibitory Activities - Ramírez-Cisneros, M. Ángeles; Rios, María Yolanda; Ríos-Gómez, Ramiro; Aguilar-Guadarrama, A. Berenice (Planta Medica, 2012)
Krameria pauciflora is a species belonging to the Krameriaceae family. It has been used to treat inflammatory disorders in folkloric Mexican medicine; however, chemistry and pharmacological studies have not been carried out on this species. In this work, from the dichloromethane root extract of K. pauciflora, five cycloartane-type triterpenoids were isolated: cyclomargenyl-3-O-β-caffeoyl ester (1), cyclomargenyl-3-O-β-feruloyl ester (2), cyclomargenyl-3-O-β-coumaroyl ester (3), cyclomargenol (4, polysthicol), and cyclomargenone (5). Additionally, the lignane 6′-methoxyrataniaphenol was isolated. To the best of our knowledge, compounds 1–3 are new natural products, whereas compounds 4 and 5 are isolated for the first time in the Krameria genus and the Krameriaceae family. The structures of all of these compounds were established by 1D and 2D NMR spectroscopy including 1H, 13C, DEPT, COSY, HSQC, and HMBC experiments, as well as by EI mass spectrometry. There is an incomplete previous report about the spectroscopic data of compounds 4 and 5. However, in this work, a complete and unambiguous assignation has been realized. Due to the traditional use of this plant and other species from this genus, such as K. lappacea, cycloartanes isolated herein were evaluated by their inhibition of phospholipase A2, cyclooxygenase-1, and cyclooxygenase-2 enzymes. Cyclomargenyl-3-O-β-caffeoyl ester (1) showed inhibition of phospholipase A2, cyclooxygenase-1, and cyclooxygenase-2 target enzymes for nonsteroidal anti-inflammatory drugs. Both cyclooxygenases were inhibited by cyclomargenol (4); however, cyclomargenyl-3-O-β-feruloyl ester (2) showed inhibition only on cyclooxygenase-1.
Keywords: Krameria pauciflora; Krameriaceae; cycloartanes; cyclomargenol; PLA2; COX-1; COX-2